Optical Characterization of Mineral Dust from the EAIIST Project with Digital Holography - Claudia Ravasio (11372020); Llorenç Cremonesi (11372023); Claudio Artoni (11372026); Barbara Delmonte (2427214); Valter Maggi (2427220); Marco A. C. Potenza (11372029) (2021)
We describe an optical approach based on Digital Holography for single-particle characterization of mineral dust and micrometric particles, focusing on the analysis of airborne particles in meltwater from Antarctic ice cores. We record the holograms formed by the superposition of the transilluminating reference beam and the waves scattered by single particles. Taking a cue from recent approaches in the field and holography methods, we process the holograms to recover both optical and morphological properties of single dust grains. As a considerable advantage over traditional light-scattering-based methods, holograms give the extinction cross section of each particle and, by numerically reconstructing the wavefront propagation, an unambiguous image of each particle whereby we derive its cross-sectional shape and size. Measurements have been carried out on samples collected from the recent EAIIST (East Antarctic International Ice Sheet Traverse) project, some of which show evidence of volcanic events. The vast majority of the detected particles show significant deviations from the isometric shape, as confirmed by both image reconstruction and extinction cross section analysis. By our analysis, we observe that experimental data have an extinction cross section up to 3 times lower than that of spherical particles with the same volume. Therefore, these deviations have an appreciable impact on the aerosol contribution to radiative forcing: retrieving particle shape may improve the modeling of the radiative properties of mineral dust and reduce the associated uncertainties.